Lack of association between venous hemodynamics, venous morphology and the postthrombotic syndrome after upper extremity deep venous thrombosis. (March 2015) - Czihal, M; Paul, S; Rademacher, A; Bernau, C; Hoffmann, U
Objectives: To explore the association of the postthrombotic syndrome with venous hemodynamics and morphological abnormalities after upper extremity deep venous thrombosis. Methods: Thirty-seven patients with a history of upper extremity deep venous thrombosis treated with anticoagulation alone underwent a single study visit (mean time after diagnosis: 44.4 ± 28.1 months). Presence and severity postthrombotic syndrome were classified according to the modified Villalta score. Venous volume and venous emptying were determined by strain-gauge plethysmography. The arm veins were assessed for postthrombotic abnormalities by ultrasonography. The relationship between postthrombotic syndrome and hemodynamic and morphological sequelae was evaluated using univariate significance tests and Spearman's correlation analysis. Results: Fifteen of 37 patients (40.5%) developed postthrombotic syndrome. Venous volume and venous emptying of the arm affected by upper extremity deep venous thrombosis did not correlate with the Villalta score (rho = 0.17 and 0.19; p = 0.31 and 0.25, respectively). Residual morphological abnormalities, as assessed by ultrasonography, did not differ significantly between patients with and without postthrombotic syndrome (77.3% vs. 86.7%, p = 0.68). Conclusions: Postthrombotic syndrome after upper extremity deep venous thrombosis is not associated with venous hemodynamics or residual morphological abnormalities.